Concussion in contact sport: investigating the neurocognitive profile of Afrikaans adolescent rugby players - Horsman, Mark (Rhodes University, Faculty of Humanities, Department of Psychology, 2010)
A number of computerised tests have been especially developed to facilitate the medical management of the sports-related concussion. Probably the most widely used of these programmes is the ImPACT test that was developed in the USA and that is registered with the HPCSA for use in the South African context. A recent Afrikaans version of the test served as the basis of the present study with the following objectives: (i) to collect Afrikaans ImPACT normative data on a cohort of Afrikaans first language adolescent rugby players with Model C education for comparison with existing South African English first language adolescent rugby players with Private/Model C schooling, and (ii) to investigate the pre-versus postseason ImPACT neurocognitive test profiles of this cohort of Afrikaans first language adolescent rugby players versus equivalent noncontact sports controls. The results for Part 1 of the study generally demonstrate poorer performance in respect of the Afrikaans cohort, which is understood to be the result of poorer quality of education. The results for Part 2 demonstrated failure of the rugby group to benefit from practice on the ImPACT Visual Motor Speed composite score to the same extent as the control group. It is argued that this apparent cognitive vulnerability in the rugby group is due to lowered cognitive reserve capacity in association with long term exposure to concussive and sub-concussive injury.
Keywords: Afrikaner students -- Intelligence testing; Sports -- Psychological aspects; Rugby football injuries; Neural computers; Neuropsychological tests; Brain -- Concussion